Estudo das propriedades diéletricas em reações de hidrólise ácida do bagaço de cana-de-açúcar e seu uso na modelagem de reatores assistidos por micro-ondas - Vasconcelos, Leonardo Gomes de (2018)
The present study aimed to design prototypes of optimized microwave reactors based on measurements of dielectric properties of reactional media involved in the acid hydrolysis of sugarcane bagasse with sulfuric acid in the presence or not of glycerin as co-solvent and its consequences on the geometry of microwave-induced reactors. The reactors proposal was based on results of dielectric properties of 0.3 to 13.5 GHz, of the hydrolysis reactions of sugarcane bagasse by sulfuric acid, varying reaction parameters, such as: temperature, time, concentration of the acid, the bagasse:water mass ratio and the use of co-solvent (glycerin). From the measurements of the dielectric properties, in an unprecedented way, and evaluating the reaction parameters of the hydrolysis reactions and the specific influences of the reagents, it was evidenced the conductivity domain in the dielectric loss process and its great dependence on the concentration of sulfuric acid, regardless of any other variation in the reaction medium. The values of ε′ and ε″ calculated the loss tangents and the penetration depths at 0.915 and 2.45 GHz, and also, in an unprecedented way, it was possible to obtain the solutions of the boundary conditions for cylindrical reactors operating in monomode in TM - (Transverse Magnetic) and TE - (Transverse Electric) to 0.915 and 2.45 GHz and thus to determine the best propagation modes for each frequency and the diameters of wells (Dc) and diameters of samples (Da) for these modes, in function of the reaction medium, the possibility of coupling the specific guides at each frequency with the reactor and the higher mass capacity of the reaction mixtures. Thus, for both frequencies 0.915 and 2.45 GHz was obtained as the best mode of propagation the TM, having the following dimensions of reactor: Dc of 25 cm, Da of 10 cm and height of 25 cm for monomode 0.915 GHz; Dc of 12 cm, Da of 11 cm and height of 12 cm for monomode 2.45 GHz; and for multimodes at 2.45 GHz a Dc of 25.95 cm and height of 25.95 cm. From these dimensions, three reactor proposals were carried out for reactions of acid hydrolysis of sugarcane bagasse with glycerin as co-solvent, induced by microwave, of which a monomode in 0.915 GHz TM, a monomode in TM 2.45 GHz and a 2.45 GHz multimode.